Implementasi Kepemimpinan Kepala Sekolah dalam Membina Kompetensi Sosial Guru - Bradley Setiyadi; Mohamad Muspawi; Ristia Kasiani (Universitas Indraprasta PGRI Jakarta, 2021)
The principal as a leader must be able to increase empowerment and guidance for teachers through improving human resource management. Therefore the principal has the obligation and responsibility to develop teacher competence. This study aims to describe the supporting and inhibiting factors for the implementation of the principal's leadership in building up teacher social competence. This research was conducted at SMA Negeri 7 Kerinci using descriptive qualitative research methods with case study research. Data collection techniques in this study were observation, interviews, and documentation studies. The data presentation analysis technique started from the collection of all data from observations, interviews, and documentation studies. Then it was followed by data reduction, data presentation and conclusions drawn. While the data validity test used data triangulation. The results of this study indicated that: 1) Guidance in communication and socializing effectively in SMA Negeri 7 Kerinci was good enough with the implementation of picket sympathy for all school elements. 2) The development of school and community relationship management and taking an active role in the community was good enough with the implementation of synergy-building guidance for teachers at SMA Negeri 7 Kerinci. 3) Guidance in preparing teachers as agents of social change was good enough with the existence of MGMP guidance for all school elements in SMA Negeri 7 Kerinci. Meanwhile, the inhibiting factor in developing teacher competence in SMA Negeri 7 Kerinci was the lack of initiative of the principal and teacher awareness in providing guidance to improve social competence for teachers.